Forward and Backward Detectable Gray-Scale Data Storage System in Polymeric Material. (29th September 2009) - Sungur, E.; Carrara, D.; Taupier, G.; Fort, A.; Mager, L.; Barsella, A.; Dorkenoo, K. D.
Abstract : We describe a fast way to encode a gray-scale image with quadratic properties in polymer thin film doped with azo dye. Under a two photon microscopy setup, we induced disorientation in corona-poled azo dye copolymer thin films by a focused near infrared (IR) femtosecond laser beam of variable exposure time. In situ, the sample was then scan to detect the second harmonic signal. We have also tested the backward detection which can provide reading and writing through a single microscope objective. In addition, we were able to store binary 3D information in the bulk of a 50 μ m thick film of the same material.